Spatial-temporal analysis of land use and the impact of tidal flooding: A case study on the north coast of Semarang City, Indonesia - Utami, Westi; Wijayanti, Tri Ida; Fuadina , Lutfia Nursetya (Brawijaya University, 2026)
The examination of land-use dynamics is crucial to enhancing land utilization and promoting economic development and environmental sustainability. The objective of this study was to examine the spatiotemporal dynamics of land use and its impact on the agricultural sectors. The employed research methodology was a mixed-methods approach, incorporating spatial analysis of land-use changes and qualitative descriptive methods. This study utilized images captured by the Sentinel satellite in 2015, 2020, and 2025. Land use change analysis was conducted using an overlay. Interpretation was then performed under the supervision of a maximum-likelihood algorithm, and the accuracy of the analysis was assessed using a confusion matrix. Meanwhile, a qualitative descriptive analysis was conducted to formulate a mitigation strategy to prevent further land degradation from tidal flooding. The results indicated that between 2015 and 2025, there were significant changes in land use, with residential areas expanding by 155 ha and industrial areas by 78 ha. Furthermore, the study revealed a 63-ha decline in mangroves, leading to the destruction of coastal barriers and a 26-ha increase in tidal flooding. The findings of this study demonstrated that the dynamics of land use brought on by tidal floods not only cause flooding and damage to infrastructure and settlements, but also result in the loss of land for agricultural and fish pond production, which provide a living for local people. Research indicates that the consequences of climate change result in substantial losses, necessitating the urgent integration of climate change considerations into development and spatial planning.